(RE)CONCEPTUALIZING LINEAR EQUATIONS: A SNAPSHOT FROM TEACHING AND LEARNING IN INDONESIA - Fardian, Dilham; Suryadi, Didi; Prabawanto, Sufyani; Jupri, Al (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aimed to describe the zone of concept image differences in linear equations in one variable and analyze its potential impact on mathematics learning. This research was qualitative and followed a phenomenological approach. Mathematical praxeology was used to analyze the content of the knowledge to be taught (Indonesian curriculum). In contrast, didactic praxeology was used to analyze the teaching methods involved in the taught knowledge (teacher). This study explores information obtained from human and non-human sources. The object of the study was a seventh-grade mathematics textbook used in Indonesian middle schools, which refers to the Merdeka curriculum. The results showed differences in concept image between scholarly knowledge, knowledge to be taught, and knowledge regarding the topic of linear equations in one variable. Teachers failed to understand the information provided in the mathematics textbook that the equal sign in the concept of a linear equation in one variable represents a quantitative equation, meaning the expression on the left side of the equal sign is equal to the expression on the right side of the equal sign. This research presents an alternative praxeological reference model as an implication for the field of education in Indonesia, allowing students to generate new knowledge as justified true belief independently. Policymakers can also utilize the model to design linear equations in one variable materials that are more aligned with students' abilities by providing a structured approach that takes into account the students' prior knowledge and learning pace.